Threshold Decision Adaptive Modulation and Coding schemes for OFDM communications - Moustafa, M.M.A. (2009 IFIP International Conference on Wireless and Optical Communications Networks, 2009)
This paper presents a Threshold-Decision Adaptive Modulation and Coding (TD-AMC) technique for OFDM systems. The proposed technique makes the transmitter changes the order of the modulation on each sub-carrier separately depending on the BER on this sub-carrier at the receiver side. The simulation results show an overall average gain in the BER performance of the proposed technique of normal fixed order modulation techniques.